Comparison of Clinical and Microbial Profile of Osseointegrated Implants and Natural Teeth: A Pilot Study - D’Souza, 1Melba Lisa; Nagarathna, DV; Wavhal, Poonam (Journal of Orofacial Research, 2014)
Implants have become an important alternative to conventional prosthesis for the replacement of missing teeth. With increasing demand for dental implants, failure is also being reported more frequently. Several factors, such as bacterial infection and excessive occlusal stress, are associated with the occurrenceof the disease and influence microbial composition. Present treatment for gingival inflammation is directed at the removal of bacterial plaque or reduction of microbial composition. In case of implants this will not hold true. It is necessary to assess the biology and pathology of peri-implant tissues. Hence, this studyis aimed at comparison of clinical and microbiological status of osseointegrated implants with that of a natural tooth.